2015
DOI: 10.1159/000374027
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Promotes Beta Cell Proliferation via PI3k/Akt Signalling Pathway

Abstract: Background/Aims: Prevention of diabetes requires maintenance of a functional beta-cell mass, the postnatal growth of which depends on beta cell proliferation. Past studies have shown evidence of an effect of an incretin analogue, Exendin-4, in promoting beta cell proliferation, whereas the underlying molecular mechanisms are not completely understood. Methods: Here we studied the effects of Exendin-4 on beta cell proliferation in vitro and in vivo through analysing BrdU-incorporated beta cells. We also analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The PI3K signaling pathway serves a dominant role in the regulation of β-cell function ( 12 ), which is orchestrated by an intricate network of mediators. AKT/PKB, acting as a downstream target of PI3K, regulates the proliferation of β-cells through modulation of its multiple downstream genes, which include Forkhead box protein O1 (FOXO1) ( 13 ), glycogen synthase kinase-3 (GSK3) ( 14 ) and mammalian target of rapamycin (mTOR) ( 8 ), among others.…”
Section: Insulin Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K signaling pathway serves a dominant role in the regulation of β-cell function ( 12 ), which is orchestrated by an intricate network of mediators. AKT/PKB, acting as a downstream target of PI3K, regulates the proliferation of β-cells through modulation of its multiple downstream genes, which include Forkhead box protein O1 (FOXO1) ( 13 ), glycogen synthase kinase-3 (GSK3) ( 14 ) and mammalian target of rapamycin (mTOR) ( 8 ), among others.…”
Section: Insulin Signaling Pathwaysmentioning
confidence: 99%
“…Chen et al ( 13 ) argued that FOXO1 may inhibit the expression of albumin, while other proteins such as phycocyanin have been demonstrated to promote β-cell proliferation by regulating PI3K-AKT signaling and downstream FOXO1, and ameliorate diabetes mice by stimulating glucokinase expression and insulin signaling in the pancreas ( 11 , 31 ). It has also been reported that Exendin-4 may enhance β-cell proliferation in some instances by stimulating PI3K-AKT signaling, potentially via an intermediate ligand-binding activation step involving corresponding receptors ( 14 ).…”
Section: Insulin Signaling Pathwaysmentioning
confidence: 99%
“…• Increase glucose-induced insulin secretion and inhibit glucagon secretion (Drucker & Nauck 2006, Cervera et al 2008 • Increase beta-cell mass in vitro and in animal models (Kwon et al 2009, Heller et al 2011, Wang et al 2015a, however, human studies suggest no long-term effects (Bunck et al 2009) • Side effects such as nausea, vomiting and diarrhoea (Dungan et al 2014, Fineman et al 2004 • Cases of pancreatitis reported in both animal (Nachnani et al 2010, Gier et al 2012) and human studies (Ayoub et al 2010, Elashoff et al 2011, Lai et al 2015 with prolonged use • Must be delivered by injection Alpha glucosidase inhibitors (AGI)…”
Section: Biguanidesmentioning
confidence: 99%
“…Exenatide enhances glucose-dependent first- and second-phase insulin secretion via the GLP-1R downstream signaling pathway, increases β-cell mass via β-cell neogenesis and proliferation, and reduces apoptosis [ 11 ]. Exendin-4 was reported to promote β-cell proliferation via the PI3K/Akt signaling pathway, rather than the ERK/MAPK pathway, in vivo and in vitro [ 41 ]. Exendin-4 promoted the transcription of the Neurod 1 and Glut2 genes, and induced the differentiation of mouse embryonic stem cells into endocrine and insulin-producing cells [ 42 ].…”
Section: Effects Of Incretin-based Therapy On β-Cell Function and Masmentioning
confidence: 99%